Risk coping behaviour of small scale poultry farmers in Ogun State, Nigeria (2013)
Poultry farmers in Nigeria are faced with diverse forms of risks. In the absence of any form of insurance and the almost inexistent credit markets, households have devised strategies to at least mitigate the effect of these risks on their livelihoods. This study analyzed the risk-coping strategies and potential of 116 small scale poultry farmers in Ogun State. The analytical techniques used included descriptive statistics, Mean Absolute Deviation (MAD) and the Ordinary Least Square (OLS) regression model. Results revealed that the major idiosyncratic risks faced by the farmers were death of birds, high costs of inputs and low poultry production. On the other hand, the major types of covariate risks faced by the poultry farmers include outbreak of diseases, rainfall shocks and hard economic times. Coping methods that were mostly used included drawing from personal savings, rearing of resistant breeds and restocking of birds. Econometric analysis revealed that factors such as number of years of formal education of the household head, initial capital outlay and proportion of non-farm to the total monthly income had positive impacts on the risk-coping potentials of the poultry farmers. The negative impacts of factors such as household size on the potential of the poultry farmers to cope with risks were also noted. Thus, the risk behavior of farmers and the factors influencing such behavior should be considered in the design and development of effective programs for the farmers.